A Network Flow Approach for Optimizing the Passenger Throughput at an Airport Security Checkpoint. Issue 3 (April 2019) - Wang, Yiru; Zhang, Jinhua; Wang, Guipu; Wang, Yichen; Yang, Peizhou; Huang, Xiaoyin; Liu, Zhibin
Abstract: This paper is intended to solve the checkpoint throughput optimization for an International Airport. We establish a network flow structure to analyze the bottleneck of the security system.After identifying the number of each person's identity, the number of screening lanes, and the ratio of regular lanes to Precheck, we simulate the fluctuations of passenger flow, reduce the variance of waiting time and improve the passenger throughput process.